Clinical Efficacy of Silver Diamine Fluoride and Glass Ionomer Cement for Caries Arrest in Deciduous Molars - Vikas Singh; Ankita Jain; Disha Gupta; Mohammad Zanul Abedeen; Sahil Dhingra; ES Shobha; Swayam Sourav Tripathy (Advances in Human Biology, 2026)
Abstract Introduction: Dental caries remains a prevalent chronic disease in children, necessitating effective non-invasive management strategies. Silver diamine fluoride (SDF) and glass ionomer cement (GIC) are established treatments for arresting caries in primary teeth, but comparative efficacy in primary molars is underexplored. The objective of the study was to compare the 12-month clinical success of 38% SDF versus conventional GIC in arresting dentinal caries in primary molars. Materials and Methods: A randomised controlled trial enrolled 120 children (aged 4–8 years) with active dentinal caries in primary molars. Participants were allocated to SDF ( n = 60) or GIC ( n = 60) groups. Caries arrest was assessed at 3, 6 and 12 months using standardised clinical criteria (hardness on probing, absence of softness and no progression). The primary outcome was caries arrest rate at 12 months; secondary outcomes included time to arrest and adverse events. Results: At 12 months, caries arrest was significantly higher in the SDF group (91.7%) than in the GIC group (75.0%) ( P = 0.008). Mean time to arrest was shorter for SDF (2.8 ± 1.2 months) versus GIC (4.5 ± 1.8 months) ( P < 0.001). Tooth discolouration was more frequent with SDF (85%) than GIC (5%) ( P < 0.001). No serious adverse events occurred. Conclusion: SDF demonstrated superior efficacy and faster caries arrest in primary molars compared to GIC, despite greater aesthetic concerns. SDF is a viable first-line, non-invasive treatment for caries arrest, particularly in non-aesthetic contexts.